Effect of Hot Air Heating on The Cavity Temperature Distribution of Injection Mold - Do, Thanh Trung; Pham, Son Minh; Tran , Minh The Uyen; Ly, Truong Giang (Journal of Technical Education Science, 2023)
In this paper, the air-assisted mold temperature control (AMTC) is applied for heating the mold in the injection molding process. The simulation is run with the same boundary conditions in the experiment. The results shows that the AMTC can heat the surface mold plate to 171.6 °C. This temperature value is higher than the glass transition temperature of almost thermoplastic materials that used in the injection molding process. With the product thickness values of 0.1 mm, 0.3 mm and 0.5 mm, the heating rates were 6.3 °C/s, 6.39 °C/s and 6.58 °C/s, respectively. The increase in heating rate can be explained by the need for thermal energy to heat up the stamp volume that is inserted in the mold cavity for changing the product thickness. Also, the highest temperature at the top of the stamp which is nearest to the hot air gate, and the temperature is smaller when the area is far from the hot air gate.